Peluang dan Hambatan Dinas Komunikasi Informatika Statistik dan Persandian dalam mendukung program pembangunan Gubernur Sulawesi Selatan (2018-2023) - Andi Baso Achmad Pangerah; Hafied Cangara; Arianto (Syntax Literate, 2023)
The world of global information is experiencing very rapid development, which is marked by the massive and widespread use of information and communication technology by the public and makes it easier for state administrators to serve the community. Enhancement of quality management based on technology, information, and communication is the wrong effort by the government to create transparency and not quite enough to answer maintenance. Matter This is required to increase the ability of the government to provide services to the public. The priority program of the South Sulawesi Provincial Communication Informatics and Encoding Office in an effort to support the vision and mission of the Governor of South Sulawesi in the Regional Medium Term Development Plan (RPJMD) of the South Sulawesi Province is "South Sulawesi that is Innovative, Productive, Competitive, Inclusive, and Characteristic". Program Development and Implementation for e-Government as well as the ‘Baruga Layanan publik’ Development Program Local government must improve the quality of communication related to various programs and activities and ensure that they are accepted, followed, and obeyed by the community. So far, the use of the media is still lacking, especially in the South Sulawesi Provincial Government. Several local and national media outlets are increasingly dominated by leader news, while OPD activities that are directly related to people's lives are not well coordinated and distributed. Especially when it comes to the realization of priority programs.